The Literary Labour of Ants: Refabulation, Digression, and Utopian Form in Daniel Sada’s Porque parece mentira la verdad nunca se sabe (1999) - Gutiérrez Negrón, Sergio (Humanimalia, 2024)
This essay considers the literary labour carried out by ants in Daniel Sada’s Porque parece mentira la verdad nunca se sabe (1999), considered one of the most significant works of Mexican literature in the last decade of the twentieth century. This essay takes a digressive scene within the novel, in which an ant fable is imagined, as a model of “refabulation”, a rewriting of Western formic, or ant-centred, narratives that attempts to escape the total enclosure of allegory. Sada’s refabulation both registers the fact of ants’ radical alterity and deploys them as the axis for the articulation of a utopian desire for the potential of a collective life organized beyond scarcity, labour, and capitalism. At the same time, the essay suggests that meaningful representations of interspecies interactions might not be found in novelistic narratives per se, but in the digressions often found and contained in its pages.